Environmental literacy, the key to sustainable conservation of wetlands in urban areas - Cain NZVERE; Lovemore CHIRUBVU; Thebeth MASUNDA (Smart Cities and Regional Development Journal)
The study focuses on understanding human effect on urban development and wetland degradation in Harare and Chitungwiza, Zimbabwe. Wetlands are a crucial ecosystem as various living things depend on them for their survival and existence. In Africa, particularly Zimbabwe, continued existence of wetlands is under threat due to human activities, such as construction of houses, urban farming and waste dumping. There are limited conservation efforts in place to save the resourceful wetlands whose benefits to human beings and other various living species are immeasurable. This study was conducted in Seke in Chitungwiza, Warren Park and Mufakose in Harare where wetlands are affected by human activities. The study explores the effect of urban development on environmental sustainability due to urbanisation. A qualitative approach was adopted where 30 households were engaged in in-depth interviews. The study highlighted various reasons for residing, farming and dumping waste on wetlands.Moreover, the study explores challenges associated with living in wetlands,while showcasing the limitedlevels of environmental literacy among residents regarding wetlands and environmental conservation. Major gaps have been realised on environment literacy and policies that govern environmental conservation and these were identified as the main factors contributing towards continued wetland degradation in the three areas under the study. The study concluded that individuals are more concerned with their primary needs of securing food and shelter, with little or no consideration of the after effects of such on the environment which include individual heath, as well as depreciation of other services and goods found in wetlands. Recommendations have been put forward to ensure that literacy levels are increased and more importantly, comprehensive and binding policies should be put in place to enforce the conservation strategies.